Blood-Brain Barrier Opening in Alzheimer's Disease Using MR-guided Focused Ultrasound. (1st September 2019) - Meng, Ying; Shirzadi, Zahra; MacIntosh, Bradley; Heyn, Chris; Smith, Gwen S; Aubert, Isabelle; Hamani, Clement; Black, Sandra; Hynynen, Kullervo; Lipsman, Nir
Abstract: INTRODUCTION: The blood-brain barrier (BBB) represents a significant restriction to therapeutic delivery to the central nervous system. Several techniques are available to circumvent the BBB, however focused ultrasound does so noninvasively and under image-guidance. MR-guided focused ultrasound (MRgFUS) in combination with intravenous microbubbles has been shown in animal models to transiently open the BBB, enhance biological therapeutics, and lead to greater reductions in Alzheimer disease (AD) pathology. Leveraging this preclinical data, we test, for the first time, whether MRgFUS induced increase in BBB permeability is safe, feasible, and repeatable in patients with early-to-moderate AD. METHODS: Five patients with AD (mean age 66.2, mean MMSE 22.6) were recruited to this phase I open-label study. Two MRgFUS procedures targeting the right dorsolateral prefrontal cortex were performed 1-mo apart. [18F]-florbetaben PET was used to confirm amyloid deposition at the target site before the procedure. Patients were followed for 3 mo. Safety was assessed by the number and quality of adverse events. Feasibility was qualitatively assessed by gadolinium contrast extravasation in the target immediately and 1-d postprocedure. Resting state functional MRIs (rs-fMRIs) and [18F]-florbetaben PET were additionally acquired as exploratory measures. RESULTS: Immediate gadolinium extravasation after MRgFUS demonstrated increased BBB permeability. This resolved the morning after. BBB open was uniform and achievable on all occasions. Opening the BBB did not result in serious clinical or radiographic adverse events, as well as no clinically significant worsening on cognitive scores at 3 mo compared to baseline. [18F]-florbetaben PET analysis suggested no group-wise changes in amyloid deposition at the target postsonication. There was a significant temporary decrease in functional connectivity in the ipsilateral frontoparietal network, with no additional long-term changes in frontoparietal or default mode network. CONCLUSION: Our results provide the basis for the next investigation of MRgFUS as a potential novel treatment and therapeutic delivery strategy for patients with Alzheimer's disease. Exploratory analysis of advanced imaging further suggests ultrasound is capable of noninvasive neuromodulation.